The Eternal Debate Over Conservatism and Prudence: A Historical Perspective on the Conceptualization of Asymmetry in Financial Accounting Theory* - Orthaus, Selina; Pelger, Christoph; Kuhner, Christoph (Contemporary Accounting Research, 2023)
ABSTRACT The recent revisions of conceptual frameworks (CFs) by the IASB and the FASB included changes to the status of prudence/conservatism, accompanied by a broader debate about the meaning and role of asymmetry in financial accounting theory (FinAT). This paper adopts a historical perspective to identify possible sources of the current controversies by examining how the discourse on asymmetry has developed over time. For this purpose, we trace the conceptualization of asymmetry in FinAT building from the 19th century until 2018, covering contributions to the US FinAT literature and the conceptual reasoning of standard setters (and their constituents) in the United States and at the international level. We identify four distinct constructs of asymmetry (ultra‐, specified, discretionary, and neutral asymmetry) developed in FinAT under the headings of “conservatism” and/or “prudence.” Our analysis reveals that the respective historical circumstances strongly influenced which notion and role of asymmetry were commonly accepted in FinAT, while the arguments underlying the debates were going in circles and were characterized by an increasing level of abstraction over time. We conclude that the controversy about asymmetry is partially due to conceptual ambiguity but also due to different assumptions about the objective of financial reporting and attributes of the preparer, which are indicative of two conflicting paradigms shaping the FinAT discourse on asymmetry. Our findings point to gaps and limitations in the deductive CFs currently employed by the IASB and FASB. Our study highlights future research potential regarding the construction of the preparer in standard setting and analyses of the ways in which deductive CFs (fail to) translate into consistent standards.